Evaluation of Some HYV Boro Rice Varieties for Drought Tolerance Based on Morpho-Biochemical Traits - Md Sohel Rana,; Md Abdul Wahed Khan,; Shah Tasdika Auyon,; Mohammad Amdadul Hoque,; Kazi Rifat Shahrin,; Md Nuruzzaman,; Muhammad Javidul Haque Bhuiyan,; Sharif Ar Raffi, (Research in Agriculture Livestock and Fisheries, 2024)
An experiment was conducted to study the drought tolerance in selected boro rice varieties in pots at the Farm Research Laboratory of Dept. Genetics and Plant Breeding, Bangladesh Agricultural University, Mymensingh in Rabi season of 2014-2015. In this experiment, drought was induced by manipulating the field capacity (30-35% FC as drought, 95-100% FC as control) and moisture content of the soil in the pot. Drought treatment was started 36 days after transplanting and continued till harvest. The work was comprised based on several morphological and biochemical approaches viz. days to 50% flowering, plant height, panicle length, no of total tillers hill-1, no of effective tiller hill-1, days to maturity, no of filled grains panicle-1, no of unfilled grains panicle-1, grain panicle-1, 100 seed weight, grain yield panicle-1, yield hill-1, spikelet fertility, proline and L-ascorbic acid were found to be changed significantly in drought stress as compared to the control. In drought conditions, the highest yield performance was showed in BRRI dhan29 by changing 33.11% compared to its control. Due to drought induction proline accumulation was significantly upregulated by 2.53 and 2.10 folds in BRRI dhan36 and BINA dhan5, respectively and L-ascorbic acid was decreased lowest in BINA dhan10, BRRI dhan50, and BRRI dhan29 by 27.29%, 41.31%, and 43.91%, respectively. This study produced substantial information about the drought tolerance status of the selected boro rice varieties, and therefore, can be an aid for any future attempt to improve the drought tolerance of the studied varieties. Vol. 10, No. 3, December 2023: 247-258